(untitled) (Asian Journal of Social Science Studies, 2018)
Several research have shown that nonattachment, a Buddhist practice, could reduce negative emotions and improve positive emotions (Sahdra & Shaver, 2013; Sahdra, Shaver, & Brown, 2010; Wang, Wong, & Yeh, 2016; Wendling, 2012). We aimed to explore such influences in a sample of Vietnamese Buddhists (N = 472). Our methods included the State Trait Anxiety Inventory (STAI; Spielberger et al., 1983), the Nonattachment Scale (NAS; Sahdra et al., 2010), and a demographic and religious questionnaire. Results showed that positive emotion scores (M = 2.89, SD = .502) of participants were significantly higher than that of their negative emotion scores (M = 2.10, SD = .587, p < .001). People with strong religious commitment such as monks, lay-people who practiced at pagoda, and lay-people who practiced with sangha had higher positive emotion scores and less negative emotion scores than those whose religious commitment were weak. Nonattachment was positively correlated with positive emotions (r = .47, p < .01) and negatively correlated with negative emotions (r = -.37, p < .01). Nonattachment could also explain 21.7% positive emotions variance (p < .001) and 12.4% negative emotions variance (p < .001). Nonattachment and religious commitment could, therefore, influence greatly positive emotions in Buddhists. This result suggested a discussion about applying nonattachment to prevent emotional problems and improve psychological well-being.